A Strategic Perspective on Social Trust and Consumer Purchase Intention: Conceptual Insights and Future Research Directions - Wahyuni, Amalia; Vitria, Aida (Yayasan Sinergi Kawula Muda, 2025)
This study aimed to map the conceptual structure of the relationship between social trust and consumer purchase intention. This study uses a bibliometric approach based on data from the Scopus database. The articles analyzed were 376 journal articles and proceedings published between 2000 and 2025, using English and relevant to the research theme. The data selection method used the PRISMA approach to ensure the accuracy and relevance of the studies analyzed. Bibliometric analysis was carried out using Bibliometrix-R and VOSviewer software to visualize research trends, thematic evolution, and the distribution of dominant keywords. The study results showed that the publication trend on social trust and purchase intention has experienced rapid growth, especially in digital marketing, social media, and e-commerce. Some of the main themes that emerged include the role of online reviews (electronic word-of-mouth), influencer credibility, and the influence of online communities in building consumer trust. In addition, this study identified research gaps, especially in the influence of artificial intelligence algorithms on the formation of social trust, as well as how trust in the digital environment can increase customer loyalty in the long term. Suggestions for further research include further exploration of AI-based personalization in building trust, the impact of data protection regulations on consumer trust, and more effective community-based marketing strategies.